Cross‐sectional and longitudinal associations between subcutaneous adipose tissue thickness and dual‐energy X‐ray absorptiometry fat mass. (22nd September 2021) - Green, Jacob J.; Smith, Robert W.; Stratton, Matthew T.; Harty, Patrick S.; Rodriguez, Christian; Siedler, Madelin R.; White, Sarah J.; Williams, Abegale D.; Dellinger, Jacob R.; Keith, Dale S.; Boykin, Jake R.; Tinsley, Grant M.
Abstract: The present study examined cross‐sectional and longitudinal relationships between total and segmental subcutaneous tissue thicknesses from ultrasonography (US) and total and segmental fat mass (FM) estimates from dual‐energy X‐ray absorptiometry (DXA). Traditional US FM estimates were also examined. Twenty resistance‐trained males (mean ± SD; age: 22.0 ± 2.6 years; body mass: 74.8 ± 11.5 kg; DXA fat: 17.5 ± 4.5%) completed a 6‐week supervised resistance training programme while consuming a hypercaloric diet. Pre‐ and post‐intervention body composition was assessed by DXA and B‐mode US. Data were analysed using Pearson's correlation ( r ), Lin's correlation coefficient (CCC), paired t ‐tests, Wilcoxon signed‐rank tests and Bland–Altman analysis, as appropriate. Cross‐sectionally, correlations were observed between total DXA FM and total subcutaneous tissue thickness ( r = 0.88). Longitudinally, a correlation was observed between total DXA FM changes and total subcutaneous tissue changes ( r = 0.49, CCC = 0.38). Correlations of similar magnitudes were observed for the upper body and trunk estimates, but DXA FM changes were unrelated to subcutaneous tissue changes for the lower body and arms. Cross‐sectionally, US 2‐compartment FM and DXA FM were correlated ( r = 0.91, CCC = 0.83). Longitudinally, a weaker correlation was observed ( r = 0.47, CCC = 0.33). In summary, longitudinal associations between US and DXA are weaker than cross‐sectional relationships; additionally, correlations between US subcutaneous tissue and whole‐body DXA FM appear to be driven by the trunk region rather than appendages. Reporting raw skinfold thicknesses rather than FM estimates alone may improve the utility of techniques based on subcutaneous tissue thickness, such as US and skinfolds.